Anti-Müllerian hormone and luteinizing hormone for prediction of spontaneous ovulation after laparoscopic ovarian drilling in clomiphene-resistant polycystic ovary syndrome - Mohamed Rezk; Mohamed Emarh; Alaa Alhalaby (Middle East Fertility Society Journal, 2016)
Objectives: Correlation between pre-ovarian drilling anti-Müllerian hormone (AMH) and luteinizing hormone (LH) levels and subsequent spontaneous ovulation following the procedure. Methods: Prospective observational study including 113 primary infertility, clomiphene resistant patients with polycystic ovary syndrome (PCOS) in the department of Obstetrics and Gynecology, Menoufia University Hospital, Egypt. The selected patients were directed to have laparoscopic ovarian drilling (LOD). Ovulation was diagnosed by serial follow-up ultrasonography in the subsequent cycles confirmed by day 21 progesterone. AMH and LH assays were done before and 3 months after the procedure. Receiver operator characteristic (ROC) curve was used to correlate between patients’ characteristics and hormonal profile and spontaneous ovulation following LOD. Results: Using ROC to assess the prognostic value of AMH and LH, it was found that AMH ⩾ 8.5 ng/ml was associated with no ovulation after LOD (sensitivity 74% and specificity 69%, with area under the curve (AUC) of .797 and p-value < 0.001). Also, LH ⩾ 15.2 IU/l was associated with no ovulation after LOD (and sensitivity of 71% and specificity of 73% with AUC of .792 and p-value < 0.001). Conclusions: Pre-drilling AMH and LH levels could be useful predictors of spontaneous ovulation after LOD. Further larger studies are warranted to confirm these findings.